Endovascular therapy for critical limb ischemia. (April 2015) - Dominguez, Arturo; Bahadorani, John; Reeves, Ryan; Mahmud, Ehtisham; Patel, Mitul
Abstract : Critical limb ischemia (CLI) represents an advanced disease state of peripheral arterial disease. It manifests as lower extremity ischemic rest pain or ischemic skin lesions leading to ulceration or gangrene. Patients with CLI often have multiple medical comorbidities and a 1-year mortality rate of 25% and a 1-year amputation rate of 25%. Historically, bypass surgery with autogenous veins for flow restoration has been the first-line therapy for CLI. However, advances in endovascular techniques and device technology have changed the treatment paradigm. Catheter-based technologies are rapidly evolving at a rate that is outpacing large-scale studies evaluating relevant clinical outcomes. Patients with CLI require a multidisciplinary management approach centered on aggressive medical therapies, wound care and prompt revascularization, with an emphasis on limb salvage. This review summarizes the contemporary endovascular therapies including balloon angioplasty, atherectomy and bare-metal stenting. In addition, we review emerging technologies, such as drug-eluting stents, drug-coated balloons and chronic total occlusion recanalization devices.